A WEB-BASED BUDGET CONTROLLING INFORMATION SYSTEM USING LARAVEL FRAMEWORK (Case Study: PT. Tangki Raya) - Duan Je Martiko Manurung; Pratyaksa Ocsa Nugraha Saian (UNIVERSITAS STEKOM, 2022)
Tangki raya is a company whose main business is steel design and pipe infrastructure. It is required to manage and maintain the amount of funds and labour when a project is underway, the difficulty of those requirement increases as the project increases in scale. Therefore, the Budget Controlling system will help alleviate work load of mantaining the funds and management of labor in order to increase efficiency and convenience. Using Laravel Framework to build a web based appliaction will help in accessibility and provide ease of use. Application development uses the prototyping model and responses aquired from user based testing. From the result of 30 respondents the system that has been develop proves to give lessen of work load, convenience and a comprohensive interface.